PERBANDINGAN SISTEM FONOLOGI BAHASA MINANGKABAU DI DESA TALAWI HILIR KECAMATAN TALAWI DENGAN DESA KOLOK NAN TUO KECAMATAN BARANGIN KOTA SAWAHLUNTO PROVINSI SUMATERA BARAT - Halimiyah Halimiyah; Ermanto Ermanto; Novia Juita (Faculty of Languages and Arts, Universitas Negeri Padang, 2014)
This article was written to compare the Minangkabau language phonology system in Villages Talawi Hilir with Villages Talawi Kolok Nan Tuo, based on: (1) vokoid and its distribution, (2) kontoid and its distribution, (3) diphthongs and its distribution, (4) deret vokoid and its distribution, (5) cluster and its distribution, as well as (6) deret kontoid and its distribution. The method used is descriptive method. Research Data in the form of the words spoken by people in Village Talawi Hilir and Village Kolok Nan Tuo with instruments 200 basic vocabulary Morris Swades and 200 basic cultural vocabulary. These Data are collected using the simak methods and cakap method. Findings this research is as follows.First, language Minangkabau in the Village Talawi Hilir and Villages Kolok Nan Tuo both have 10 vokoid.Second, language Minangkabau in the Village Talawi Hilir and Villages Kolok Nan Tuo both have 21 kontoid.Third, language Minangkabau in the Village Talawi Hilir has 9 diphthongs, while village Kolok Nan Tuo has 11 diphthong.Fourth, languageMinangkabau in the Village Talawi Hilir have 14 the vokoid, while village Kolok Nan Tuo having 16 the vokoid.Fifth, not found any cluster in both this village.Sixth, language Minangkabau in the Village Talawi Hilir and Villages Kolok Nan Tuo has 11 the kontoid.